Bird frugivory on palm oil Elaeis guineensis Jacq. (Arecaceae) in the Costa do Dendê, Valença, Bahia, Brazil - Lima, Diego Mendes; Neves, Edinaldo Luz das; Machado, Caio Graco (SITIENTIBUS série Ciências Biológicas, 2007)
The present study was carried out in Cajaíba (13º22’08"S; 39º04’20"W), Valença, BA, between September 2004 and August 2005 and it had as objective to determine which birds consume the fruits of Elaeis guineensis Jacq. (Arecaceae). Fruits eaten were noted by focal-individual observation. We registered the number of fruits removed, tactics of capture, feeding behaviors and intra- and interspecific agonisms. In a total of 99 visits, 18 bird species were registered eating the fruits. The species that presented the highest rate of removal were Thraupis palmarum (Wied, 1823) (28.2%), Tersina viridis (Illiger, 1811) (12.9%), Myiozetetes similis (Spix, 1825) (10.6%), and Tachyphonus rufus (Boddaert, 1783) (10.6%). The most used tactics of capture was “picking the food without the total extension of the legs or the neck” and the most common behavior of mandible was “removing portions, taking away the fruits and making the seeds fall on the soil, near the plant. Gnorimopsar chopi (Vieillot, 1819) and Icterus jamacaii (Gmelin, 1788) were considered potential dispersers, because they transported the fruits far from the mother plant. Interspecific agonisms were registered between Tyrannus melancholicus Vieillot, 1819 and M. similis and between T.palmarum and T. viridis.